Analysis of Elementary Teachers Understanding on Ijen Geopark - Reizal, Haidhar; Sujana, Atep; Sopandi, Wahyu (International Conference on Elementary Education, 2022)
This study aimed to analyze and explain the understanding of elementary school teachers in Bondowoso Regency on Ijen Geopark. This study used a descriptive research method with a qualitative approach. The data collection instrument used a questionnaire. The respondents of this study were elementary school teachers in grades I-VI in Bondowoso Regency, totaling 60 elementary school teachers, namely 19 male teachers and 41 female teachers spread over 17 districts from 23 districts in Bondowoso Regency. The results showed that the understanding of elementary school teachers in Bondowoso Regency was considered good in comprehending Ijen Geopark as an integrated local content of thematic learning in schools. This is proven by the total score of elementary school teachers' understanding of Ijen Geopark of 3216. Based on this, it can be concluded that elementary school teachers in Bondowoso Regency have an understanding of Ijen Geopark with a score percentage of 77% and are included in the "good" category. Therefore, elementary school teachers are considered ready to integrate Ijen Geopark local content in thematic learning and are able to carry out thematic learning that links Ijen Geopark as local content in schools.